2019
DOI: 10.1080/1744666x.2019.1574571
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term real-world effectiveness of omalizumab in severe allergic asthma: systematic review of 42 studies published 2008-2018

Abstract: Introduction: Omalizumab is a recombinant monoclonal anti-IgE antibody approved in the US as add-on treatment in moderate-to-severe allergic asthma (in severe allergic asthma [SAA] in Europe). A 2016 review of 24 real-world effectiveness studies in SAA published between 2008-2015 concluded that omalizumab was associated with significant improvements in objective and subjective outcomes with benefits extending beyond 2 years. Several new real-world studies have been published since, bringing the total to 42 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 86 publications
4
44
0
8
Order By: Relevance
“…Although short‐term safety data are reassuring, more accurate reporting is warranted, in combination with long‐term safety evaluation, including observational studies and registries . For omalizumab, there are good data available to support its efficacy and safety in the paediatric population; however, for benralizumab and dupilumab the data are limited highlighting the urgent unmet need for rigorous trials with biologicals in severe asthma in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Although short‐term safety data are reassuring, more accurate reporting is warranted, in combination with long‐term safety evaluation, including observational studies and registries . For omalizumab, there are good data available to support its efficacy and safety in the paediatric population; however, for benralizumab and dupilumab the data are limited highlighting the urgent unmet need for rigorous trials with biologicals in severe asthma in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of improvement of severe eosinophilic asthmatics with mepolizumab in our cohort is similar to the one reported with omalizumab in severe allergic asthma in a recent review 27 . The reduction in exacerbations was however higher in our real‐life study with mepolizumab than that reported previously with omalizumab.…”
Section: Discussionmentioning
confidence: 99%
“…One review of the literature, (80) evaluating 25 RCTs involving patients with moderate to severe allergic asthma, showed that omalizumab, when compared with a placebo, reduced the exacerbations by approximately 25%, decreased the number of hospitalizations, and allowed a slight reduction in the dose of ICS. A systematic review of 42 real-life studies, (81) two of which were conducted in Brazil, (82,83) showed that omalizumab improved asthma control, reduced the number of emergency room visits/hospitalizations, and allowed the use of lower doses of OCS and ICS.…”
Section: Omalizumabmentioning
confidence: 99%